Caracterização físico química do fruto e produção de vinagre de Physalis pubescens L - Melo, Leonardo Wilezelek Soares de (2013)
Physalis is a genus of plants of the same family as potato and tomato (Solanaceae), which has very peculiar characteristics and produces a fruit and fleshy coloration varies from green to orange. An expansion in the cultivation of physalis would be an alternative to producing small and medium size, since the cultivation of it is relatively easy. However fruits are rich in vitamins, especially C and flavonoids are little known for people and may be used in the production of vinegar. This work was performed physicochemical characterization of juice and wine from the fruits of Physalis pubescens, and quantified total and reducing sugars, protein, pH, total soluble solids and vitamin C. After alcoholic fermentation of juice or vinegar was obtained, with the same characterized with respect to pH, vitamin C, acidity and soluble solids.